The Method of Viral Mimicry in Oncology and Prospects for its Improvement - R. N. Mustafin (SINAPS LLC, 2023)
Malignant neoplasms cells are characterized by clonal evolution that is resistant to the applied antitumor drug and evasion from the effects of the immune system. Therefore, a promising direction in modern oncology is the stimulation of the immune response against neoplasms. This method can be used in combination with other anticancer drugs and alone. Tumor cells produce CTLA4 (CTLA4 - cytotoxic T-lymphocyte protein 4) and PD-1 (programmed cell death) checkpoints that inhibit the activity of T-lymphocytes and their production of antitumor cytokines. The clinic uses antibodies against CTLA4, PD-1 and PD-L1, monotherapy with which increases the effectiveness of the chemotherapy used, but significantly aggravates the development of adverse reactions, which limits their use. Monotherapy with anti-PD/PD-L1 showed low efficacy and also a high risk of pulmonary, hepatic, and thyroid complications. In this regard, it is necessary to develop new methods of tumor immunotherapy. The most promising in this regard is the method of viral mimicry, when double-stranded RNA formed from transcripts of retroelements serve as a trigger for the production of interferon and activation of T-killers. For artificial activation of retroelements, inhibitors of DNA methyltransferases, deacetylases, and histone methyltransferases are used. Since retroelements are located in gene introns, viral mimicry can be used in spliceosomal targeted therapy. Transposons serve as drivers of carcinogenesis, therefore, in addition to their artificial activation, oncology uses methods for silencing retroelements using reverse transcriptase inhibitors. The use of non-specific methyltransferases and inhibitors of histone demethylases for this can lead to suppression of the expression of other genes, with possible side effects. Therefore, this technique is the most promising with the use of guides that direct histone modification enzymes to the loci of the location of retroelement genes in the genome. Guides can also be used to activate the most significant retroelements in the development of the immune antitumor response and exclude the expression of elements involved in the initiation and maintenance of carcinogenesis. MicroRNAs, long non-coding RNAs, and antisense oligonucleotides can be used as guides.